Lean and Ecological Warehousing - Faltusová, Kristýna; Martínez, Felipe; Čillík, Jan; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2025)
The thesis examines how Lean Six Sigma and eco-friendly practices can be combined to improve operations and the sustainability of a warehouse in an SME. Using the DMAIC framework, the study aimed to identify inefficiencies specifically in the retailer-focused warehouse. Through tools like SIPOC, spaghetti diagrams, and a flowchart, two CTQs were selected for an analysis: First- time yield and Space utilization. It has been found that longer process times contribute to more errors and thus lower FTY, and that inconsistent layout and lack of standardization contribute to less efficient space utilization. Improvement proposals include not only lean recommendations, such as layout reorganization based on ABCXYZ analysis or a subsequent adoption of a WMS system, but also sustainable recommendations, such as LED lights, digital documentation, or an electric forklift. Based on the research, the study concludes that while not all sustainable measures have a positive impact on the warehouse performance, lean improvements indirectly contribute to the sustainable performance through waste elimination and transport reduction.
Vedoucí práce: Felipe Martínez
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2025
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2025
Způsob přístupu: Internet
Keywords: international management [obor dipl. práce]; diplomové práce; master's theses